The Saxicolous Lichens of Bilyi Kamin Track (Zacharovanyi Krai National Nature Park, Ukrainian Carpathians) (CHORNOMORSKI BOTANICAL JOURNAL, 2025)
Question: Which lichens grow on silicate rocks in the Bilyi Kamin tract in the Zacharovanyi Krai National Nature Park? Location: Zakarpattia region, Ukraine Materials and methods: field research, microscope technique Nomenclature: Index Fungorum https://www.indexfungorum.org/ Results: The article presents the results of lichenological studies of volcanic rocks in the Bilyi Kamin tract, located within the Zacharovanyi Krai National Nature Park. In total, 33 lichen species belonging to 26 genera were found on volcanic rocks. Eight of these species (Arthrorhaphis citrіnella, Brianaria sylvicola, Immersaria athroocarpa, Lepraria cfr. borealis, L. rigidula, Micarea lithinella, Porpidia hydrophila, and Trapelia placodioides) are reported for the first time from the Volcanic Carpathians. The sorediate variety Glaucomaria rupicola var. efflorens is also reported for the first time from Ukraine. Brianaria sylvicola was known from only one locality on Mount Yavirnyk in Transcarpathia, based on a collection that was almost a century old. However, the report of Immersaria athroocarpa is the first confirmation of its presence in over 60 year Previously, only two locations in Ukraine were known to host the lichen Porpidia hydrophila, while only three locations were recorded for the species Trapelia placodioides. The paper demonstrates the distribution of lichens on volcanic rocks under the influence of exposure and water regime within the tract. A hypothesis is put forward that the name of the rock, Bilyi Kamin (White Stone), is associated with its white colour, caused by the dominance of the lichen Varicellaria lactea.
Keywords: biodiversity, fungi, species, volcanic rocks, Zakarpattia region, Ukraine